Downtown change almost total - Pappas, Mike (Raton, NM Raton Range, 1989)
Columns written by Mike Pappas, owner of the Sweet Shop Restaurant, for the Raton Daily Range on a wide variety of topics, some historical, some current, some personal.
Newspaper Article by Mike Pappas List of local businesses and locations from 1948 can be seen in attached image
Master list item #: 84
File location is in the Raton File Cabinet
Keywords: Life and Customs; Local History; Local Businesses; Raton, New Mexico